Odpowiedzi

Najlepsza Odpowiedź!
2010-01-29T16:47:44+01:00
∛x = x^⅓, √ x = x^½

∫{[x³ -∛x]/√x} dx = ∫(x³/√x)dx - ∫(∛x/√x)dx =
=∫[x³/(x^½)]dx -∫ [x^⅓ / x^½] dx =
= ∫ x^(⁵/₂) dx - ∫ x ^(-¹/⁶) dx =
=[ x^(⁵/₂ +1)]/[⁵/₂ +1] + [ x^(-¹/₆ +1)]/[-¹/₆ +1] + C =
= [ x^(⁷/₂)]/(⁷/₂) + [x^(⁵/₆)]/(⁵/₆) + C =
= (2/3) x^(⁷/₂) + (6/5) x^(⁵/₆) + C

∫ [ 1/x + 1/cos²x + 2√x ] dx = ∫[1/x]dx + ∫[1/cos²x]dx +2∫√x dx =
= ln I x I + tg x + 2*∫ x^(¹/₂) dx = ln I x I +tg x +2{[ x^(³/₂)]/(³/₂)} +
+ C = ln I x I + tg x + (4/3)*x^(³/₂) + C
x^a oznacza x do potęgi o wykładniku a.
ln - logarytm naturalny